(untitled) (Bangladesh Medical Journal, 2016)
This descriptive cross-sectional study was carried out on 384 third year medical students from 6 government and 6 non-government medical colleges to find out the opinion regarding newly introduced assessment system in the 1st professional MBBS examination which was held in January 2012. It was found that majority (75%) of the respondents expressed their satisfaction with the newly introduced assessment system. Ninety one percent students opined that short answer question in written examination had inclined students to understand content rather than memorization. Eighty nine percent and eighty six percent respondents expressed their opinion in favor of MCQ and objective structured practical examination respectively. Majority (82.03%) students opined that inclusion of structured oral examination (SOE) instead of traditional oral exam was better. Nearly 87% respondents thought that adding of a certain percentage of mark of formative assessment was a positive initiative. On the other hand, 35% students felt that examination phobia in oral or viva is not reduced by introducing SOE, 27% believed that all examination are not judged in same standard by the examiners by means of OSPE and 24% respondents believed that result of SOE depends, to some extent, upon examiners desire and intension. So, it revealed that the new assessment method is not implemented properly, teachers were not trained accordingly and students were not aware about the new assessment method. Bangladesh Med J. 2015 May; 44 (2): 92-96